A fluorescent sensor array-based electronic tongue for Chinese tea discrimination. Issue 17 (15th April 2021) - Zhu, Yanchao; Wang, Jie; Wu, Yusen; Shang, Zhikun; Ding, Yun; Hu, Aiguo
Abstract : A fluorescent sensor array-based electronic tongue consisting of 6 soluble conjugated polymeric nanoparticles (SCPNs) embedded in waterborne polyurethane was developed for 9 tea discrimination. Abstract : A fluorescent sensor array-based electronic tongue consisting of 6 soluble conjugated polymeric nanoparticles (SCPNs) embedded in waterborne polyurethane was developed for tea discrimination. 9 tea samples were discriminated by these tiny tongues on the basis of the unique fluorescence quenching effect caused by different tea components. The fluorescence quenching response results of 6 SCPNs to 9 tea samples are a synergistic work of varieties of mechanisms including the Förster resonance energy transfer. An 18-dimensional vector was obtained by recording the changes of RGB values of the sensor array, which was analyzed directly by linear discrimination analysis (LDA) to discriminate 9 tea samples along the axes of tea-manufacturing. The predicted results of this sensing system with 100% accuracy through a linear support vector machine (SVM) model suggested that the fluorescent sensor array-based electronic tongue will be a powerful tool to identify soluble analytes in the food industrial field with high accuracy and efficiency.